Germline MUTYH (MYH) mutations in Portuguese individuals with multiple colorectal adenomas - Isidro, G (2004)
Germinal mutations in the base excision repair (BER) gene MUTYH (MYH) have recently been described in association with predisposition to multiple colorectal adenomas and cancer. In contrast to the classic dominant condition of familial adenomatous polyposis (FAP) due to germinal mutations in the APC gene, the MYH polyposis is an autosomal recessive disease. The identification of individuals affected by MYH polyposis brings new and important implications for the diagnostic, screening, genetic counseling, follow up and therapeutic options in these patients. In this study, screening for germinal mutations in the MYH gene was performed in 53 Portuguese individuals with multiple colorectal adenomas or classic adenomatous polyposis, in whom no mutation had been identified in the APC gene. The results revealed the presence of biallelic germline MYH mutations in 21 patients. In addition, we here report 3 mutations (c.340T>C [p.Y114H]; c.503G>A [p.R168H]; and c.1186_1187insGG [p.E396fsX437]) which, to our knowledge, have not been previously described